Housing development and management - Ghosh, Santosh; Gupta, Ranajit; Gupta, Sumita; Centre for Built Environment (Calcutta, India).; International Workshop on Housing Development & Management Centre for Built Environment) (1994. (Calcutta Centre for Built Environment, 1996)
Papers presented at the International Workshop on Housing Development & Management organized by Centre for Built Environment, held in December 9-11, 1994 at Calcutta.
Keywords: Housing development -- Congresses; Housing management -- Congresses